Ethlix Sport Centre Enterprise - Zakaria, Nur Haswani; Mohd Nazri Nazar @ Azizan, Nur Afiqah; Fauzi, Nur Adibah; Ahmad Kamaruddin, Nur Afiqah; Ahmad Zalizan, Nur Azlisha Farhana (2019)
Ethlix is a partnership business which has been founded in 2019 in Bandar Cassia, Pulau Pinang. Ethlix consist of 5 founder and will be launch in 2022. Ethlix is basically a sport centre which offer variety of sport services such as badminton and squash. There will also be a sport equipment store at the ground floor of our building. We also offer a hotel service for our visitor who want to stay at our sport centre.